The Specter of Judeo-Christianity and the Politics of Gender Deviancy: From St. Paul of Tarsus to St. Paul, MN (Relegere: Studies in Religion and Reception, 2012)
With the 2012 presidential campaign monopolizing the national conversation, the present moment offers an ideal vantage point from which to reflect on the inescapable shadow of the "Judeo-Christian Tradition" in American political discourse. Nowhere, perhaps, is this imposing shadow more apparent than in the politics of sexuality. This essay explores the presence of deviant sexuality in American politics from two angles. I consider first the varied uses of the Judeo-Christian tradition to conjure a terrifying menace of rampant decadence threating to undo national stability. Second, I compare the rhetorical strategies apparent in this modern discourse with the poetics of gender deviancy in ancient Jewish and Christian contexts, probing the continuities and discontinuities evident in these two discursive contexts.